Pengolahan Obat Kumur-Kumur Dari Ekstrak Bunga Kecombrang - Cut Fatimah; Safriana; Nurhayuna; Eka Febriyanti; Muhammad Aldi Risky; Nur Indah Nazwa Hary; Yuliana (STIKES Columbia Asia Medan, 2025)
Poor oral health is often caused by inadequate oral hygiene, leading to conditions such as bad breath and periodontal disease. Bingkat Village, located in Pegajahan Subdistrict, Serdang Bedagai Regency, is predominantly inhabited by farmers, with many housewives lacking productive activities to support their families’ income. This community service program aimed to provide training for PKK (Family Welfare Movement) women on producing mouthwash using natural ingredients, particularly torch ginger extract, which is known to contain antibacterial compounds. The implementation methods included educational sessions, hands-on training, and assistance with product formulation, packaging, and marketing. The results indicated an improvement in participants’ understanding and skills in producing herbal mouthwash, as well as the emergence of economic opportunities through the development of local products.